2004
DOI: 10.1002/cncr.20098
|View full text |Cite
|
Sign up to set email alerts
|

Restaging surgery for women with borderline ovarian tumors

Abstract: We studied the clinical impact of neutralizing antibodies to botulinum toxin A that occurred during long‐term treatment of children between 1993 and 2001. Antibodies were found in high titers in 35 of 110 (31.8%) samples from individual patients. Antibody formation correlated with secondary nonresponse (p < 0.001). The most significant risk factors for antibody formation were the frequency of treatments (p = 0.0001) and the injection of a higher weight‐adapted maximum dose per treatment (p = 0.001).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
1
20

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(101 citation statements)
references
References 70 publications
6
74
1
20
Order By: Relevance
“…According to our results, in 9 -20% of the evaluated hospitals, a pelvic, and in 3 -7%, a para-aortal lymph node dissection were performed. These data are in accordance with other international trials (Fauvet et al, 2004;Cusido et al, 2007;Kumpulainen et al, 2007).…”
Section: Surgical Therapysupporting
confidence: 93%
See 2 more Smart Citations
“…According to our results, in 9 -20% of the evaluated hospitals, a pelvic, and in 3 -7%, a para-aortal lymph node dissection were performed. These data are in accordance with other international trials (Fauvet et al, 2004;Cusido et al, 2007;Kumpulainen et al, 2007).…”
Section: Surgical Therapysupporting
confidence: 93%
“…Moreover, it is not yet clear whether these lymph node implantations represent real metastases, in situ transformed secondary muellerian epithelia or hyperplastic mesothelial cells (Shiraki et al, 1992;Chang et al, 2008). Concerning the performing of lymph node resection, at least 20% of the patients with FIGO stage I have to be upgraded as belonging to FIGO stage IIIc, but the prognostic relevance is in our opinion unimportant (Fauvet et al, 2004;Sehouli et al, 2005a, b;Silva et al, 2006). According to our results, in 9 -20% of the evaluated hospitals, a pelvic, and in 3 -7%, a para-aortal lymph node dissection were performed.…”
Section: Surgical Therapymentioning
confidence: 86%
See 1 more Smart Citation
“…Concerning the restaging procedure, retrospective studies have shown that, even when such staging procedures are performed, they have no impact on survival in patients with BTO. [21][22][23] However, if there are no descriptions regarding the abdominal cavity and peritoneal surfaces, restaging is recommended because in 39% of BTO, the omentum is involved and 9% have invasive implants. 24 On the other hand, in cases of over-diagnosis, surgeons have concerns about fertility-preserving surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies show that, even when such staging procedures are performed, they have no impact on the survival (9,32). In patients in whom surgery has been performed for presumed benign disease and there is no description of the abdominal cavity and peritoneal surface, we do recommend restaging because in 39% of BOTs, the omentum is involved, with 9% invasive implants (33).…”
Section: Restaging Proceduresmentioning
confidence: 99%